Strategi Keuangan dan Operasional dalam Mendorong Pertumbuhan Laba: Studi pada Sektor Kesehatan Perusahaan Terdaftar di BEI - Astuti, Dewi Ratnasari; Aliyah, Irpa Hilmatul; Riswandi, Dede (Politeknik Raflesia Press, 2024)
The purpose of this study is to determine how capital structure, cash turnover, and inventory turnover influence profit growth, both partially and simultaneously. The sample consists of companies in the healthcare sector from 2019 to 2022. Quantitative data is the type of data used in this research. Secondary data and an associative research type are employed as data sources. This study uses a purposive sampling method to analyze data from 13 companies, resulting in 52 financial reports as the sample. The analysis technique involves multiple regression analysis with the assistance of SPSS version 25. The empirical findings of this study indicate that inventory turnover and capital structure have a positive partial influence on profit growth. However, cash turnover does not explain profit growth. Based on simultaneous testing, capital structure, cash turnover, and inventory turnover collectively have a positive influence on profit growth.